PreImplantation Factor (PIF*) endogenously prevents preeclampsia: Promotes trophoblast invasion and reduces oxidative stress. (April 2016) - Barnea, E.R.; Vialard, F.; Moindjie, H.; Ornaghi, S.; Dieudonne, M.N.; Paidas, M.J.
Highlights: PIF secreted by viable embryos, expressed in placenta and maternal circulation. PIF promotes trophoblast invasion: early preeclampsia prevention potential. PIF prevents oxidative stress and protein misfolding: late preeclampsia prevention potential. Abstract: Preeclampsia is a unique pregnancy disorder whose patho-physiology is initiated early in gestation, while clinical manifestations typically occur in mid-to-late pregnancy. Thus, prevention should optimally be initiated in early gestation. The intimate interaction between PIF, secreted early by viable embryos, and its host-mother provides insight into putative mechanisms of preeclampsia prevention. PIF is instrumental at the two critical events underlying preeclampsia. At first, shallow implantation leads to impaired placentation, oxidative stress, protein misfolding, and endothelial dysfunction. Later in gestation, hyper-oxygenation due to overflow of maternally derived oxygenated blood compromises the placenta. The first is likely involved in early preeclampsia occurrence due to reduced effectiveness of trophoblast/uterus interaction. The latter is observed with later-onset preeclampsia, caused by a breakdown in placental blood flow regulation. We reported that 1. PIF promotes implantation, endometrium receptivity, trophoblast invasion and increases pro-tolerance trophoblastic HLA-G expression and, 2. PIF protects against oxidative stress and protein misfolding, interacting with specific targets in embryo, 3. PIF regulates systemic immunity to reduce oxidative stress. Using PIF as an early preventative preeclampsia intervention could ameliorate or even prevent the disease, whose current main solution is early delivery.